2019
DOI: 10.3168/jds.2018-15774
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activities of Maillard reaction products from whey protein isolate fermented by Lactobacillus gasseri 4M13 in lipopolysaccharide-stimulated RAW264.7 cells

Abstract: Maillard reaction products formed from whey protein isolate (WPI) and sugar have been shown to have an anti-inflammatory effect in vitro. Here, we incubated WPI and galactose (GWA) in an aqueous solution at 65°C for 24 h to produce a glycated conjugate, which was then fermented using Lactobacillus gasseri 4M13 to obtain the fermented product (F-GWA). We demonstrated that F-GWA had an anti-inflammatory effect on lipopolysaccharide (LPS)-stimulated RAW264.7 cells. It reduced both LPS-stimulated nitric oxide prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Pro-inflammatory macrophage accumulation is an important feature of IBD, including ulcerative colitis [37]. In our previous experiment, RAW264.7 macrophages treated with LPS produced less NO when pre-treated with FMRP, and because it inhibited the phosphorylation of ERK and JNK in response to LPS-induced inflammation in RAW264.7 cells, fermented MRP by 4M13 showed an anti-inflammatory effect, reducing NO production and downregulating TNF-and COX-2 gene expression [26]. Nitric oxide is often released in increased amounts in IBD, which plays a deleterious role in IBD, but NO may also exert a beneficial effect against colitis according to recent research [38].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pro-inflammatory macrophage accumulation is an important feature of IBD, including ulcerative colitis [37]. In our previous experiment, RAW264.7 macrophages treated with LPS produced less NO when pre-treated with FMRP, and because it inhibited the phosphorylation of ERK and JNK in response to LPS-induced inflammation in RAW264.7 cells, fermented MRP by 4M13 showed an anti-inflammatory effect, reducing NO production and downregulating TNF-and COX-2 gene expression [26]. Nitric oxide is often released in increased amounts in IBD, which plays a deleterious role in IBD, but NO may also exert a beneficial effect against colitis according to recent research [38].…”
Section: Discussionmentioning
confidence: 94%
“…Insulin and TNF-α levels were measured according to the manufacturers' protocols. The amount of NO in mouse serum was measured using the Griess reaction [26].…”
Section: Determination Of the Levels Of Insulin And Tnf-α And No Prodmentioning
confidence: 99%
“…Therefore, in this study, the immune cells were assumed to have higher cytokine protein levels if the corresponding mRNA levels were higher. Kim et al (2019) reported that fermented products from MR-conjugated whey protein using Lactobacillus gasseri 4M13 have improved anti-inflammatory effects on RAW 264.7 cells, reducing NO production and inflammatory cytokine expression compared with the nonfermented MRP. Other studies also found that fermented MRP-derived whey protein hydrolysate improved antioxidant activity, cardiovascular prevention activity, and NK cell activity (Oh et al, 2014;Kang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During the heat treatment process (i.e., boiling, sterilization, and drying), chemical changes in milk can occur, which can result in a nonenzymatic browning reaction between sugar and protein known as the Maillard reaction (MR; van Lieshout et al, 2020). It has been reported that MR decreases the total allergenicity of β-LG (Perusko et al, 2018;Yang et al, 2020) and generates various benefits including increasing its byproducts' antioxidant and immunomodulatory activities (Yáñez et al, 2018;Kim et al, 2019;Liu et al, 2019;Chun et al, 2020;Xiang et al, 2021). It is also worth mentioning, however, that the MR can lead to the development, by oxidative stress and diabetes (Nooshkam et al, 2020), of advanced glycation end products (AGE) such as methylglyoxal-derived AGE.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is that sulfites can condense with amino compound after additional reaction with reducing sugars, thus inhibiting the whole reaction (Gogus, Wedzicha, & Lamb, 1997). In the actual production process, MR should be controlled according to the needs of the product (Kim, Chun, Oh, Lee, & Lee, 2019). Based on the above factors, we can summarize the measures to control the degree of MR by (1) removing one of the reactants: the corresponding enzymes such as glucose invertase can be used, or calcium salts can be added to combine with amino acids to form insoluble compound; (2) lowering the inverse temperature or pH modulation to slightly acidic; (3) maintaining the low moisture content in food; (4) adding sulfites at the initial stage of the reaction (Wedzicha, Bellion, & German, 2005).…”
Section: Factors Affecting Mr and Mrpsmentioning
confidence: 99%